Power with nature : renewable energy options for homeowners - Ewing, Rex A. (PixyJack Press, Inc., 2012)
"Covers renewable energy options for grid-tied and off-grid homeowners, including solar energy (passive and active), wind power, microhydro energy, geothermal heat pumps, solar water heating, biomass heating, backup generators and pumping/storing water. Also examines energy conservation, system sizing/pricing, and tax incentives"--